2014
DOI: 10.1038/cdd.2014.22
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Zebrafish Noxa promotes mitosis in early embryonic development and regulates apoptosis in subsequent embryogenesis

Abstract: Noxa functions in apoptosis and immune system of vertebrates, but its activities in embryo development remain unclear. In this study, we have studied the role of zebrafish Noxa (zNoxa) by using zNoxa-specifc morpholino knockdown and overexpression approaches in developing zebrafish embryos. Expression pattern analysis indicates that zNoxa transcript is of maternal origin, which displays a uniform distribution in early embryonic development until shield stage, and the zygote zNoxa transcription is initiated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In zebrafish, the apoptotic response is activated during development at 8 hpf (45) as zBik, a key factor in regulating apoptosis, is not expressed until 8 hpf (46). In this study, apoptosis was observed at 6 hpf in the prmt6 morphants (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…In zebrafish, the apoptotic response is activated during development at 8 hpf (45) as zBik, a key factor in regulating apoptosis, is not expressed until 8 hpf (46). In this study, apoptosis was observed at 6 hpf in the prmt6 morphants (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…The mRNA was synthesized by using Message Machine-Kit (Ambion). The microinjections were performed as described previously (Liu et al, 2009;Zhong et al, 2014).…”
Section: Morpholino Oligonucleotides Constructs and Mrna Injectionsmentioning
confidence: 99%
“…(Tissue-Tek), then the testes were sectioned at 5 μm with a cryostat microtome (Leica) and immunofluorescence detection was performed as described (Dong et al, 2004;Peng et al, 2009;Zhai et al, 2014). At last, images were viewed and acquired under confocal microscopy (NOL-LSM 710 Carl Zeiss) as described Zhong et al, 2014).…”
Section: Western Blot and Immunofluorescence Localizationmentioning
confidence: 99%